The effects of spacer grid arrangement on flow boiling characteristics and critical heat flux in a complex 5 × 5 rod bundle channel. (November 2022) - Wang, Xusheng; Liu, Yingwen
Abstract: In this study, a numerical model of two-phase flow boiling in a rod bundle channel was developed to investigate the influence of spacer grid's arrangement on thermal-hydraulic characteristics and critical heat flux (CHF). It was verified well by comparing with the experimental data obtained from 2006 look-up table, and the relative errors were within ±20% in most conditions. On this basis, taking a complex 5 × 5 rod bundle channel as an example, four different geometric models including bare rod bundle, rod bundles with upstream, downstream and two-Span spacer grid were established, respectively. It was found that upstream spacer grid has little influence on CHF, while CHF could be significantly improved by downstream spacer grid. Convective heat transfer coefficient of liquid phase can be increased a lot at the region of spacer grid, but enhancement effect of heat transfer only keeps a limited distance as the decreases of mixing effect of mixing vane. According to the distribution of secondary flow, the intensity of secondary flow caused by upstream spacer grid is weakened at the region of downstream spacer grid. Moreover, spacer grid would result in an increase of pressure drop, causing a certain pressure on the pump load.